(untitled) (Al-Aasar, 2025)
Since the time, Ghulam Ahmad Pervaiz fell in server love of socialism and in mental lassitude of westernism, he began to distort the meaning of Quranic words, and then, alter the real sense of the Quranic verses. He did so, either as a concomitance of his strong amorousness of newly accepted cult, or merely to be on solo flight against the Muslim scholar. المزمل is among those Quranic words, when feel victim to his distortion and alteration during his lexiconal research, he deviated from the real meaning of this word المزمل verses. Knowingly or un-knowingly, he perverted the real sense of this word, due to the change of genuine measure (i.e تَفَعُّلُ) into false measure (i.e تفعیل). So following this pattern, he substituted المزمل with undue measure التزمیل, resulting in un-necessary confusion in his discussions in the sense of Quranic verses. Mr. Ghulam Ahmad Pervaiz seems to be a perpetual addict to such deliberate alteration. However, the writer of this article has tried his level best, not only, to highlight the real meaning of المزمل , but also to expose defects, flaws, deficiencies and discrepancies, found in research of Mr. Ghulam Ahmad Pervaiz. To earn fame and popularity among Muslim people, Mr. Ghulam Ahmad Pervaiz got himself in deep research of Quranic teachings, for about fifty years, as a result of which, he wrote, several books, that added feathers to his reputation. His literature won great acceptance from the western secular and atheist scholars, but an intense oppistion and repugnance from the theological Muslim scholars of all over the Muslim world, due to the fact, that Mr. Ghulam Ahmad Pervaiz absolutely mis-interpretted by the Holy Quran, based on his Quranic lexicon لغات القرآن , full of falsification, because the meaning of Quranic words in this book لغات القرآن , have mercilessly been altered.